Das utopische Europa: Die Verträge der politischen Integration Europas und ihre utopischen Elemente - Koch, Marcus (transcript, 2015)
What is the role of utopia in the process of European integration? What does the term »Utopian Europe« mean in times of economic and financial crises in the EU? By analyzing its fundamental legal texts, Marcus Koch points out the position of utopian ideas in European unification, and how they have changed through the course of history. Once more, this study shows that utopian ideas are a driving force of political processes, and contributes to the discourse about the attractiveness and sensibility of the now heavily scolded European Union.